KUALITAS PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIDOARJO - Hafidh Leviyanto (DIA: Jurnal Administrasi Publik, 2018)
Dispendukcapil to increase user service satisfaction in order to attract public enthusiasm in managing population administration. The ultimate goal of increasing user service satisfaction is to achieve the target of ownership of population documents and civil registration. The forms of activity innovation that are being promoted by Dispendukcapil Sidoarjo Regency in their regular services are the Package System. The Package System is the process of managing one deed document but getting one or two other documents automatically. The deed document includes a birth certificate, death certificate, marriage or divorce while the other two documents include the Family Card (KK) and the new ID Card (KTP). In this program, when someone arranges a birth certificate, he will automatically get a new KK. Another example, when someone takes care of a divorce certificate, then he automatically gets a new KK and KTP.Based on this background, the problems that can be formulated are how the dimensions of tangible, reliability, responsiveness, assurance, and empathy influence on the satisfaction of service users in the Population Office and Sidoarjo Regency Civil Registration? This study uses quantitative methods and used theories from Parasuraman and Berry Zeithaml who found that ten dimensions. The rezult are user satisfaction of Dispendukcapil Sidoarjo Regency service is influenced by 4 dimensions and supports the Pasuraman theory. The effect of the assurance dimension is not possible because this dimension is considered not too important by service users. This is in line with the characteristics of the Dispendukcapil respondents in Sidoarjo Regency who mostly earn Rp. 1.2 Million, with a high school education background and job seekers.